Planejamento estratégico e cultura de inovação no setor público : uma análise do PDI no IFRS, campus Bento Gonçalves - Lorenzon, Claudia (My University, 2026)
Building a culture of innovation in the public sector requires alignment between strategic guidelines, shared values and everyday organisational practices. This dissertation examines the extent to which the Institutional Development Plan (PDI) 2024?2028 of the Instituto Federal do Rio Grande do Sul (IFRS), Bento Gonçalves campus, fosters an innovation-oriented organisational culture, and identifies the mechanisms through which strategic planning connects with institutional values, norms and practices. The study proceeds from the premise that the PDI's capacity to drive change does not arise automatically from the formalisation of its guidelines, but is mediated by leadership, communication, organisational structure and incentive mechanisms. Three specific objectives were established: to identify the main obstacles to consolidating a culture of innovation; to examine how innovation is addressed within the PDI, assessing the alignment between guidelines and targets; and to analyse staff perceptions of the PDI's role in promoting innovative practices and in consolidating institutional values conducive to transformation and organisational learning. The focus on the Bento Gonçalves campus is justified by its having the largest workforce within IFRS and by its encompassing the four educational modalities established by Law Nº11.892/2008, which makes it analytically representative of the challenges of managing innovation. The research adopts a qualitative approach, with a single-case study design, combining documentary analysis of the PDI 2024?2028, the 2024 Management Report, the 2024 Actions and Results Report (RAR) and the Internal Evaluation Committee (CPA) Reports (2024 and 2025) with ten semi-structured interviews conducted with academic and administrative staff. Data were analysed using Discursive Textual Analysis (Análise Textual Discursiva, ATD), supported by NVivo 15, yielding 512 units of meaning distributed across nine analytical categories. The findings indicate that the PDI relates to organisational culture in differentiated ways: at the structural level the relationship is moderate, since innovation appears formally in the strategic axes and in monitoring through indicators, although these do not capture cultural aspects; in the symbolic and behavioural dimensions the relationship is still nascent, as innovation has yet to function as a shared value and innovative initiatives remain sporadic and dependent on individual motivation. The main obstacles include bureaucratic rigidity, the absence of formal mechanisms for recognising innovation, and top-down communication. It is concluded that the PDI fulfils its normative role and part of its symbolic role, but does not yet operate as a driver of deeper cultural transformation, pointing to the need to incorporate cultural indicators, rethink incentive mechanisms and broaden staff participation in the next planning cycle. [resumo fornecido pelo autor]
A construção de uma cultura de inovação no setor público exige a articulação entre diretrizes estratégicas, valores compartilhados e práticas organizacionais cotidianas. Esta dissertação analisa em que medida o Plano de Desenvolvimento Institucional (PDI) 2024-2028 do Instituto Federal do Rio Grande do Sul (IFRS), campus Bento Gonçalves, atua como indutor da cultura organizacional voltada à inovação, identificando os mecanismos pelos quais o planejamento estratégico se articula a valores, normas e práticas institucionais. Parte-se do entendimento de que a função indutora do PDI não decorre automaticamente da formalização de suas diretrizes, sendo mediada por liderança, comunicação, estrutura organizacional e mecanismos de incentivo. Foram estabelecidos três objetivos específicos: identificar os principais obstáculos à consolidação da cultura de inovação; examinar como o PDI contempla a inovação, verificando o alinhamento de diretrizes e metas; e analisar as percepções dos servidores sobre o papel do PDI na indução de práticas inovadoras e na consolidação de valores institucionais favoráveis à transformação e ao aprendizado organizacional. O recorte pelo campus Bento Gonçalves justifica-se por ser a unidade com maior quadro de servidores do IFRS e por reunir as quatro modalidades de ensino previstas pela Lei n.o 11.892/2008, conferindo-lhe representatividade analítica frente aos desafios de gestão da inovação. A pesquisa adota abordagem qualitativa, com estudo de caso único, combinando análise documental do PDI 2024-2028, do Relatório de Gestão 2024, do RAR 2024 e dos Relatórios da CPA (2024 e 2025) com dez entrevistas semiestruturadas realizadas com docentes e técnico-administrativos. Os dados foram tratados pela Análise Textual Discursiva (ATD), com apoio do NVivo 15, resultando em 512 unidades de sentido distribuídas em nove categorias analíticas. Os resultados mostram que o PDI se articula à cultura organizacional de modo diferenciado: na dimensão estrutural, o nível é moderado, pois a inovação aparece formalmente nos eixos estratégicos e no monitoramento por indicadores, embora estes não captem aspectos culturais; nas dimensões simbólica e comportamental, o nível é incipiente, pois a inovação ainda não funciona como valor compartilhado e as iniciativas inovadoras permanecem episódicas e dependentes de motivação individual. Entre os principais obstáculos destacam-se a rigidez burocrática, a ausência de mecanismos formais de reconhecimento da inovação e a comunicação verticalizada. Conclui-se que o PDI cumpre sua função normativa e parte de sua função simbólica, mas ainda não opera como indutor de transformação cultural mais profunda, sinalizando a necessidade de incorporar indicadores culturais, repensar mecanismos de incentivo e ampliar a participação dos servidores no próximo ciclo de planejamento. [resumo fornecido pelo autor]
Keywords: Planejamento estratégico; Inovação; Administração pública; Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Sul (Campus Bento Gonçalves); Strategic planning; Inovation; Public administration